2016
DOI: 10.1089/cap.2016.0048
|View full text |Cite
|
Sign up to set email alerts
|

Digital Parent Training for Children with Disruptive Behaviors: Systematic Review and Meta-Analysis of Randomized Trials

Abstract: Although additional studies are needed, DPT holds promise as a potentially scalable evidence-based treatment of children with disruptive behaviors that can save human resources.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
99
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(109 citation statements)
references
References 46 publications
9
99
1
Order By: Relevance
“…Contextual factors. Meta-analyses also show that behavioural parent training not only affects children's behaviour but also improves parental well-being (Colalillo and Johnston, 2016;Trivedi, 2017); it is as effective in routine community settings as it is specialist programme development clinics (Michelson et al, 2013); more intensive programmes are more effective (Nowak and Heinrichs, 2008); and computer-based parent training programmes can be effective for families with pre-adolescent children with clinically significant behaviour problems (Baumel et al, 2016).…”
Section: Childhood Behaviour Problemsmentioning
confidence: 99%
“…Contextual factors. Meta-analyses also show that behavioural parent training not only affects children's behaviour but also improves parental well-being (Colalillo and Johnston, 2016;Trivedi, 2017); it is as effective in routine community settings as it is specialist programme development clinics (Michelson et al, 2013); more intensive programmes are more effective (Nowak and Heinrichs, 2008); and computer-based parent training programmes can be effective for families with pre-adolescent children with clinically significant behaviour problems (Baumel et al, 2016).…”
Section: Childhood Behaviour Problemsmentioning
confidence: 99%
“…Research shows that the effects of online parenting interventions are promising. Specifically, two meta-analytic reviews have found medium intervention effects for parent and child outcomes (Baumel, Pawar, Kane, & Correll, 2016;Nieuwboer et al, 2013), which are comparable to effect sizes reported for face-to-face delivery. However, the findings of these reviews are predominantly based on data from mothers, as most studies either included only mothers or did not report the sex breakdown of parents.…”
mentioning
confidence: 58%
“…Other digital interventions have reported using automated messages or emails to interact with parents [7,24]. During the program, the coach and the parent formed a working relationship, which was crucial for meeting mutually agreed goals [25,26].…”
Section: Implementation Vs Rct Intervention 18mentioning
confidence: 99%
“…Moving interventions outside traditional clinics and into people's daily environments, like the Internet, can facilitate better access to mental health services [24].…”
Section: Implementation Vs Rct Intervention 18mentioning
confidence: 99%
See 1 more Smart Citation